Measuring Students’ Perceptions of Quality Online Learning in the Era of COVID-19 – A Case Study of Students in the Accounting Department at Taif University – - Fallatah, Rasha Abdulrhman (Journal of Economic, Administrative and Legal Sciences, 2021)
This study aimed to identify students' attitudes about distance learning in accounting courses. The study used a descriptive analysis approach, and a sample of 470 students from Taif University’s Accounting Department was selected. The results indicated that there was a positive relationship between students and their levels of satisfaction with distance learning due to their communication with each other and their teachers and the quality of education and its outcomes.
Keywords: distance education; accounting department; Taif University; Covid 19; education quality; learning outcomes